Awareness & Preference Towards Carbon Credits - An Initiative to Go for Green - Shah, Praneti (Prabandhan: Indian Journal of Management, 2010)
"What’s the use of a house if you haven’t got a tolerable planet to put it on?" This Astonishing statement of Henry David Thoreau has become a grass root reality of the earth. Now, man has the power to send rockets to Mars; Man created the wheel and rotated the whole world on it, Man has discovered life on moon but he only failed to understand a simple fact that, "The frog does not drink up the pond in which he lives". Man’s strong greed has created a threat for the environment, which has transformed the feeling, "Pride of mother earth to crime on mother earth" and has forcefully shortened the aim of human beings from "Betterment of life to just Survival of life".